Alberto Bonet and his study on the moral conscience of the child (1927): A propos of the first works on moral education at the University of Barcelona - Monserrat PAYÁ SÁNCHEZ; Conrad VILANOU TORRANO (Historia de la Educación, 2018)
In this work the authors present a historical analysis of the Catalan philosophical tradition (Ramón Martí de Eixalá, Francisco J. Llorens Barba, Tomás Carreras Artau et al.) characterised by a philosophy of the conscience and its undeniable educational consequences. If Krausism was triumphing in Madrid, in Catalonia the school of common sense was taking hold, distinguished by conscience both in the order of knowledge and in moral praxis. When Tomás Carreras Artau took over the chair of Ethics at the University of Barcelona in 1912, a Seminar began that featured the work by Albert Bonet (the future leader of Spain’s Catholic Action) on the moral conscience of the child (1927) as one of its most outstanding contributions. Although to a certain extent the Ethics Seminar was later discarded in favour of the Pedagogy Seminar which Joaquín Xirau began in 1930, it is true that the teachings of Alejandro Sanvisens (Tomás Carreras Artau’s prize pupil) permitted the configuration of a pedagogy of the conscience which is found in the roots of studies on moral education generated at the University of Barcelona by the GREM (Moral Education Research Group), founded in 1988.